ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS UNTUK PENINGKATAN SISTEM PENGENDALIAN INTERNAL PERUSAHAAN CEMARA FOOD BLITAR - Winarti, Tri (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
The aim of this study was determined the accounting information system of sales and cash receipts, and whether the accounting system of sales and cash receipts information may increase the internal control system of Cemara Food companyÂ in Blitar, this was descriptive qualitative research methods, this research was contains explanation, observation technic of data collection, interview, documentation, and data analysis technic of Miles and Huberman. The results of this study was indicated that the accounting information sales and receptions of gold was not appropriate because of the double function system, cash function held by the leadership, in which only use note or statement of account, the system already used networking procedures, the internal control system was not good because of companyâs double function structure of organization, authorization system still held by leadership, the company has not implementing good practices of current funds by deposited it into the bank, no sudden cash balance calculation . That is why the company is expected to recruit new employees for cashier, printing cash sales invoice numbered, receipts sudden cash or the next day deposited it in bank.